Solar Photochemistry for Environmental Remediation - Advanced Oxidation Processes for Industrial Wastewater Treatment - Oliveira, Anabela; Saggioro, Enrico Mendes; Pavesi, Thelma; Moreira, Josino Costa; Ferreira, Luis Filipe Vieira (IntechOpen, 2012)
None